Everyday Life in Austerity Family, Friends and Intimate Relations - Hall, Sarah Marie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book is about the impact of austerity in and on everyday life, based on a two-year ethnography with families and communities in 'Argleton', Greater Manchester, UK. Focused on family, friends and intimate relations, and their intersections, the book develops a relational approach to everyday austerity. It reveals how austerity is a deeply personal and social condition, with impacts that spread across and between everyday relationships, spaces and temporal perspectives. It demonstrates how austerity is lived and felt on the ground, with distinctly uneven socio-economic consequences. Furthermore, everyday relationships are subject to change and continuity in times of austerity. Austerity also has lasting impacts on personal and shared experiences, both in terms of day-to-day practices and the lifecourses people imagine themselves living.
Chapter 1: Introduction -- Chapter 2: Family, Friendship and Intimacy: A Relational Approach to Everyday Austerity -- Chapter 3: Everyday Social Infrastructures and Tapestries of Care in Times of Austerity -- Chapter 4: Austere Intimacies and Intimate Austerities -- Chapter 5: The Personal is Political (and Relational) -- Chapter 6: A Very Personal Crisis: Family Fragilities and Everyday Conjunctures in Austerity -- Chapter 7: Conclusion.
Keywords: Sociology; Social groups; Social structure; Equality; Human geography; Sociology of Family, Youth and Aging; Social Structure; Human Geography